Analisis Tingkat Kesehatan Keuangan Perusahaan Selama Masa Pandemi Covid-19 (Studi pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia) - Aulia Fahrunnisaa Ichwan; Samirah Dunakhir (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2022)
Â This study aims to determine the level of financial health of companies during the COVID-19 pandemic in banking companies listed on the Indonesian stock exchange. The population in this study consisted of 47 banking companies listed on the Indonesia Stock Exchange, while the sample collection technique in this study used purposive sampling where from 47 companies there were 13 companies that met the sample collection criteria and were used as samples in this study. Data collection is done by using documentation techniques. The data analysis technique uses the RGEC method, namely risk profile, good corporate governance, earnings, and capital. The results of the assessment of the level of financial soundness of banks using the RGEC method as a whole show a percentage of 79.81% and this is in Composite Rank 2 (PK-2) with criteria classified as